FENOMENA YANKI DALAM MASYARAKAT JEPANG YANG TERCERMIN PADA MANGA CROWS KARYA HIROSHI TAKAHASHI - Yuartha Putra, Desar (Humanis, 2015)
This undergraduated thesis entitled “Yanki Phenomenon in Japanese Society Reflected in Crows Manga by Hiroshi Takahashi”. The theory used for analyzing is literature sociology and supported by group characteristic, semiotic, and social pathology theories. This study aims to find out the characteristic of yanki, causative factor, and the impact of yanki phenomenon in Japanese society on Crows manga by Hiroshi Takahashi. Based on the analysis that has been done, there are three characteristics of Yanki characteristic, such as appereance characteristic, behavior characteristic, and group characteristic. The yanki phenomenon is caused by internal and external factors. The internal factors are psychological injuries or trauma, and being raised in low social environment. The external factors are environment influences and friends influences. There are also two impacts of yanki phenomenon in society, such as self impacts and society impacts.
Keywords: Japanese Society, yanki, manga